A-I-D for cascades: an application of the Behaviour Change Wheel to design a theory-based intervention for addressing prescribing cascades in primary care - McCarthy, Lisa M.; Farrell, Barbara J.; Metge, Colleen; Jeffs, Lianne; Toenjes, Sameera; Rodriguez, M. C. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Prescribing cascades, which occur when a medication is used to treat the side effect of another medication, are important contributors to polypharmacy. There is an absence of studies that evaluate interventions to address them. We describe an application of the Behaviour Change Wheel (BCW) to design theory-informed interventions for addressing prescribing cascades within interprofessional primary care teams. Methods The BCW framework was applied to guide intervention development. This report describes the first seven steps. Three behaviours were developed based on data collected from two qualitative studies exploring why and how cascades occur across practice settings. A target behaviour was selected and the COM-B model was applied to identify relevant factors for interprofessional primary care teams. Relevant intervention types, policy options, and corresponding behaviour change techniques (BCTs) were identified, and intervention examples drafted. Prioritization of behaviours and intervention examples were guided by the APEASE criteria. Results The three behaviours involved supporting: (1) healthcare providers (HCPs) to ask about, investigate and manage cascades, (2) the public to ask about prescribing cascades, and (3) the public to share medication histories and experiences with HCPs. The team selected the HCP behaviour, A-I-D (ask, investigate, deprescribe), for intervention development. Psychological capability and physical opportunity were the most relevant COM-B components. Ten intervention options comprised of BCTs were developed, which are ready for further prioritization by stakeholders. These can be grouped into: provision of educational materials for use by HCPs; provision of consultation or training to support HCPs; and knowledge mobilization strategies. Through the process, the team identified that development of a practice guidance tool, which assists HCPs to investigate and manage prescribing cascades, is needed to support further intervention development. Conclusions The BCW framework guided the design of intervention examples to support primary HCPs practicing in interprofessional teams to address prescribing cascades. When identifying interventions for future consultation, creation of a practice guidance tool was prioritized as it underpins all proposed interventions for addressing prescribing cascades in practice. Further research is needed to determine what primary HCPs would need in this practice guidance tool and how it will be used in practice, to support its development.